Single-system Langerhans Cell Histiocytosis with Skin Ulcers as the Initial Presentation - Xue-min Wang; Ye-qiang Liu; Bin Li; Ming Li; Yan Peng; Wen-cheng Jiang (Acta Dermato-Venereologica, 2024)
Abstract is missing (Short communication)